School in distance teaching. Innovation and equity - Torchia, Luca (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
Education has historically been an important mean of levelling out social inequalities in student backgrounds (Mann, 1848). Nevertheless, educational choices, performances and outcomes are affected in many aspects by the socio-economic and cultural background. The innovation linked to the entry of ICTs into the world of education had a problematic impact on the complex relationship between quality and equity of education systems. This situation has been further complicated by the recent Covid-19 pandemic. The sanitary emergency helped to increase pre-existing social inequalities and the problems related to the entry of new technologies into schools remain open.